Efficacy of Repetitive Transcranial Magnetic Stimulation for Acute Central Post-stroke Pain: A Case Study - Malfitano, Calogero; Rossetti, Angela; Scarano, Stefano; Malloggi, Chiara; Tesio, Luigi (Frontiers in Neurology, 2021)
Although rare, central post-stroke pain remains one of the most refractory forms of neuropathic pain. Repetitive transcranial magnetic stimulation (rTMS) has been reported to be effective in chronic cases. However, there are no data on the effects in the acute and subacute phases after stroke. In this study, we present a case of a patient with thalamic stroke with acute onset of pain and paresthesia who was responsive to rTMS. After a right thalamic stroke, a 32-year-old woman presented with drug-resistant pain and paresthesia on the left side of the body. There were no motor or sensory deficits, except for blunted thermal sensation and allodynia on light touch. Ten daily sessions were performed, where 10 Hz rTMS was applied to the hand area of the right primary motor cortex, 40 days after stroke. Before rTMS treatment (T0), immediately after treatment conclusion (T1), and 1 month after treatment (T2), three pain questionnaires were administered, and cortical responses to single and paired-pulse TMS were assessed. Eight healthy participants served as controls. At T0, when the patient was experiencing the worst pain, the excitability of the ipsilesional motor cortex was reduced. At T1 and T2, the pain scores and paresthesia' spread decreased. The clinical improvement was paralleled by the recovery in motor cortex excitability of the affected hemisphere, in terms of both intra- and inter-hemispheric connections. In this subacute central post-stroke pain case, rTMS treatment was associated with decreased pain and motor cortex excitability changes.